ANALISIS PENGARUH KEPUASAAN KERJA, MOTIVASI KERJA, KOMPENSASI DAN MOTIVASI KERJA TERHADAP TURNOVER INTENTION (Studi Empiris Pada Karyawan PT Home Center Indonesia Cabang Semarang) - mieftakhul fuadi (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2026)
This study will analyze the influence of job satisfaction, work motivation, compensation, and work discipline on turnover intention at PT Home Center Indonesia, Semarang Branch. The analytical tool used is multiple linear regression. However, prior to this, data instrument testing and classical assumption testing were conducted using SPSS. A census method was used for the sample size of 112 employees.The results indicate that job satisfaction, work motivation, and compensation do not have a significant effect. However, work discipline does have a significant effect on turnover intention. These results indicate that the variables job satisfaction, work motivation, compensation, and work discipline have a low contribution to turnover intention.